The fundamentals of printed textile design - Russell, Alex (Fairchild Books, 2011)
This title explores contemporary practice in printed textile design. It provides an introduction to the creative skills, techniques and processes required by designers in order to produce a professional, creative and commercially aware portfolio
Online Ausgabe erschienen bei Bloomsbury Fashion Central: 2021
Keywords: Textile design; Textile printing; Art portfolios; Textile design -- Vocational guidance; Textile printing -- Vocational guidance